White snake and other stories - Yan, Geling 1958- (Aunt Lute Books, 1999)
Stories on the Cultural Revolution by a woman writer from China. In the title story a woman prisoner falls for a handsome interrogator, only to discover the interrogator is a woman, while in Celestial Bath, a teenager turns prostitute to earn money for a ticket back to the city after her obligatory service in the country.
Aus dem Chines. übers.. - This book was funded in part by a grant from the National Endowment for the Arts"--T.p. verso
Keywords: Yan, Geling / Translations into English; Yan, Geling -- Translations into English